(untitled) - Jansson, Bruce S (Belmont, CA, 2003)
Includes bibliographical references and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: United States -- Social policy; Hoa Kỳ -- Điều kiện xã hội; Social service -- United States; Dịch vụ xã hội -- Hoa Kỳ